Profile of world agricultural cooperation.... -[19 ]- (a)
Provides a statistical overview of agricultural cooperation in 79 countries in terms of numbers of members, cooperatives and revenues. Presents detailed fact sheets on 54 countries.
Documentation Centre has: 1996